Complexity, Security and Civil Society in East Asia: Foreign Policies and the Korean Peninsula - Hayes, Peter; Yi, Kiho (Open Book Publishers, 2015)
Complexity, Security and Civil Society in East Asia offers the latest understanding of complex global problems including nuclear weapons, urban insecurity, energy, and climate change in the region. Detailed case studies in China, North and South Korea, and Japan demonstrate the importance of civil society and 'civic diplomacy' in reaching shared solutions to these problems in East Asia and beyond. Each chapter describes regional civil society initiatives that tackle complex challenges to East Asia's security. In so doing the book presents key pressure points at which civil society can push for constructive changes - especially ones that reduce the North Korean threat to its neighbors. Unusually, this book is both theoretical and practical. Complexity, Security and Civil Society in East Asia identifies strategies that can be led by civil society and negotiated by its diplomats to realize peace, security and sustainability worldwide. It shows that networked civic diplomacy offers solutions to these urgent issues in ways that official 'complex diplomacy' cannot. By providing a new theoretical framework based on empirical observation, the book is a must read for diplomats, scholars, students, journalists, activists and individual readers seeking insight into how to solve the crucial issues of our time. (Please note that the grant information as stated in the metadata below applies only to the following chapter: "6. The Implications of Civic Diplomacy for ROK Foreign Policy").